THEIOI AUTOKRATORES. A Fragment of an Honorary Inscription from the Smintheion - Tolga Özhan (Gephyra)
This article presents a fragmentary inscribed slab discovered in the sanctuary of Apollo Smintheus in 2009. The author proposes a restoration for this fragmentary inscription in the article, by comparing it with parallel epigraphic examples from Asia Minor. Ac-cording to the proposed restoration, this is an honorary inscription for a distinguished citizen of Alexandreia Troas who held many various positions, including syndikos, presbeutes, and possibly a priestly role (prophetes) in the sanctuary. Furthermore, the restored phrase theioi Autokratores is of considerable significance, as it is rarely found in inscriptions. The individual in question was send as a presbeutes on multiple occasions to the theioi Autokratores. Based on a parallel instance in Athens, it is argued in the article that the phrase theioi Autokratores (divine emperors) in the current inscription refers to the jointly reigning emperors Marcus Aurelius and Lucius Verus.